2009
DOI: 10.1111/j.1462-5822.2009.01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin A facilitates translocation of theClostridium botulinumC2 toxin across membranes of acidified endosomes into the cytosol of mammalian cells

Abstract: SummaryThe binary Clostridium botulinum C2 toxin consists of the binding/translocation component C2IIa and the separate enzyme component C2I, which mono-ADP-ribosylates actin in eukaryotic cells. Pore formation of C2IIa in early endosomal membranes facilitates translocation of unfolded C2I into the cytosol. We discovered earlier that translocation of C2I depends on the activity of the host cell chaperone heat shock protein Hsp90. Here, we demonstrate that cyclosporin A, which inhibits the peptidyl-prolyl cis/t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
118
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(126 citation statements)
references
References 47 publications
8
118
0
Order By: Relevance
“…This is in agreement with earlier findings on the translocation of the binary toxins iota-toxin and C2 toxin (3,5). Recently, we reported that the membrane translocation of some binary toxins but not of others is facilitated by host cell chaperones and PPIases (7,17,18,22). Therefore, we tested here whether CDT and the closely related iota-toxin require such factors for translocation.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This is in agreement with earlier findings on the translocation of the binary toxins iota-toxin and C2 toxin (3,5). Recently, we reported that the membrane translocation of some binary toxins but not of others is facilitated by host cell chaperones and PPIases (7,17,18,22). Therefore, we tested here whether CDT and the closely related iota-toxin require such factors for translocation.…”
Section: Discussionsupporting
confidence: 78%
“…The results corroborate our recent finding that cyclophilins and Hsp90 facilitate the membrane translocation of C2I, the enzyme component of the binary actin-ADP-ribosylating C2 toxin (22). Immunoprecipitation experiments revealed that CypA, the most abundant cyclophilin in the cytosol of mammalian cells and the major target of CsA, interacts with C2I (22). In the present study, we found that CDTa and Ia bound to the immobilized Hsp90 and CypA proteins in vitro, a hint that CypA might be the relevant cyclophilin that interacts with CDT and iota-toxin during cellular uptake too.…”
Section: Vol 79 2011supporting
confidence: 82%
See 1 more Smart Citation
“…This ratchet mechanism would thus provide the driving force for CTA1 dislocation. Although a previous report suggested the ATP-dependent dislocation of CTA1 does not require cytosolic factors (10), we and others (35,47) have detected a membrane-associated pool of Hsp90 which may have been purified with the microsomal preparation used in that study. Our work clearly shows that Hsp90 exhibits a high affinity interaction with CTA1, and that the disruption of this interaction inhibits both CTA1 dislocation and CT intoxication in vivo.…”
Section: Role Of Hsp90 In Erad-mediated Dislocationmentioning
confidence: 89%
“…To control for this possibility, we directly monitored the ER-to-cytosol translocation of transfected CTA1 in the parental TZM, TZM 1-2, and TZM 5-1 cell lines. Transfected, radiolabeled cells were partitioned into separate membrane and cytosolic fractions according to established protocols (26,29,34,45). Material immunoprecipitated from each fraction with an anti-CTA antibody was then resolved by SDS-PAGE and quantified using PhosphorImager analysis.…”
Section: Pdi-mediated Disassembly Of the Ct Holotoxin Does Notmentioning
confidence: 99%